HUBUNGAN POWER OTOT TUNGKAI DAN POWER OTOT LENGAN DAN BAHU DENGAN HASIL SMASH TIM BULU TANGKIS PB SPORTIF KECAMATAN TAMPAN - Febri Arianto; Ramadi Ramadi; Ardiah Juita (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstract: This study aims to determine whether there is a relationship between leg muscle power and arm and shoulder muscle power with the results of the Badminton Team Smash Pb Sportif, Tampan District. This type of research is a correlational study which aims to see the level of the relationship between variables, namely: the independent variable Leg Muscle Power (X1) and Arm and Shoulder Muscle Power (X2) with Smash Results (Y) on the badminton team Pb Sportif Kecamatan Handsome, numbering 14 people. Based on data that has been processed previously, it is obtained Rhitung (0.967)> rtab (0.553), meaning rcount> rtabel. It can be concluded that Ha is accepted at the significant level α = (0.05). From the results of the above analysis it can be concluded that there is a relationship between leg muscle power (X1) and arm and shoulder muscle power (X2) with the smash results (Y) of the Badminton Team of Pb Sportif, Tampan District. Key Words: Relationship of L